Development of New Biostarter Medium Using Local Raw Materials for Composting of Elephant Feces - Fitriyanto, Nanung Agus (Faculty of Animal Science, Universitas Gadjah Mada Yogyakarta, Indonesia, 2015, 2015)
The objective of this research is to develop for a new bio-starter medium for composting of elephant feces and knowing the effect on mature compost quality. Research was also designed to observe the elephant feces compost quality made with the addition of biostarter developed in rice bran fermentation (T1), biostarter made from pineapple fermentation (T2), and banana weevil biostarter (T3). The composting process was performed during a month and in every week compost materials were mixed and turned over to maintenance condition of the composting process is always aerobic. Physical parameters of compost quality were measured during 30 days of composting, chemical properties including water content, organic matter, organic carbon, organic nitrogen, organic calcium and C/N ratio were also measured. Biological observation of mature compost was observed by applying compost product on mustard growth, and the microbiological test was measured by Total Plate Count (TPC). Data were analyzed by One-way ANOVA to calculate differences among the treatments. The result showed that, significant differences (P> 0.05) was not observed on water content for all treatment that is T1 58.88%, T2 60.95%, and T3 53.40%. The Reseach parameter of the organic content was found T1 30.39%, T2 34.97%, T3 28.25%. Total organic carbon in treated compost was observed: T1 17.62%, T2 20.28%, T3 16.39%. Total Nitrogen was T1 0.44%, T2 0.43%, T3 0.51%, total P T1 0.20%, T2 0.22%, T3 0.21%, total K T1 0.77%, T2 0.80%, T3 0.88%, C/N ratio T1 39.56, T2 47.24, and T3 32.81. The biological parameters including height, number of leaves, leaf length, leaf width, root length, and weight of the harvest of mustard was also had no significant differences. Total microbial counts on mature compost were T1 9.6 x 104, T2 4.6 x 104, and T3 4.2 x 104 CFU/g.